Dampak kuota ekspor terhadap perdagangan internasional karet alam Indonesia - Dona Wahyuning Laily; Dita Atasa; Prasmita Dian Wijayanti (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: This research aimed at analyzing :1) several factors that are influencing Indonesia’s and world’s natural rubber trade performance, 2)export quota impact on Indonesia's and world’s natural rubber trade performance, 3) export quota impact on Indonesia’s natural rubber economic agent’s welfare distribution. Methods: The model used in this study uses a systems approach and uses a simultaneous equation econometric model. Results: Result of Syslin procedure in this research indicate that: 1) Several factors influencing Indonesia’s natural rubber supply significantly are the harvested area, the domestik price of palm oil and Indonesia’s natural rubber export volume. On the other hand the domestic price of Indonesia’s natural rubber is not significantly influencing Indonesia’s natural rubber supply; 2) One factor that significantly influencing Indonesia’s natural rubber price is Indonesia’s natural rubber export volume, furthermore synthetic rubber price and exchange rate are not significantly influencing the domestic price of Indonesia’s natural rubber; 3) Several factors that significantly influencing world’s natural rubber export volume are natural rubber export volume of Indonesia, Thailand and Malaysia. World’s natural rubber export volume one year ago also significantly influencing world’s natural rubber export volume; 4) Several factors that significantly influencing world’s natural rubber import volume are natural rubber import volume of USA, Japan and Chinese; 5) Several factors that significantly influencing world’s natural rubber price are synthetic rubber price and world’s natural rubber price one year ago, on the other hand world’s natural rubber export volume is not significantly influencing world’s natural rubber price. Conclusion: As a result of the quota value on exports on the welfare distribution of Indonesian natural rubber economic actors if implemented in the 2013-2019 period, the producer surplus will decrease by US 630872.283 while the consumer surplus will increase by US 89130.882 and foreign exchange earnings will decrease by US 479441 (8.506 %).